CATARACT SECONDARY TO AUTOIMMUNE UVEITIS ASSOCIATED WITH SACROILIITIS (REMUNOM, 2025)
The objective of this study was to analyze scientific articles related to autoimmune uveitisassociated with sacroiliitis with progression to cataract and to evaluate the importance of thecorrect timing of cataract surgery to obtain a satisfactory surgical result. The research was carriedout by reading articles indexed in the PubMed, SciELO and LILACS databases, published between2013 and 2025, available in free full text and without language restrictions, focusing on cataractassociated with autoimmune uveitis, phacoemulsification and sacroiliitis, using the followingdescriptors: “autoimmune uveitis”, “cataract”, “phacoemulsification”, “sacroiliitis”, “ocularinflammation”, “intraocular lens implantation”. After analyzing the specialized literature, it wasobserved that inflammatory stabilization was decisive for the success of phacoemulsification withintraocular lens (IOL) implantation, with a satisfactory visual outcome. This study reinforces theimportance of multidisciplinary management and prior control of inflammation for visualrehabilitation in eyes with a history of autoimmune uveitis.